"Harden Up and Face Reality:" Exploring Underlying Bullying Beliefs in New Zealand. (2nd January 2018) - Balanovic, Jovana; Stuart, Jaimee; Jeffrey, Jenny
ABSTRACT: A growing body of research illustrating the detrimental consequences of bullying has led to many antibullying interventions being developed. Despite good intentions, evidence suggests that such programs vary considerably in their efficacy. The current study examines the social discourse around bullying in the New Zealand environment in order to see whether underlying beliefs may undermine or influence approaches to mitigate bullying. The study employed an exploratory, qualitative approach of social discourses in the media. Using 31 online media articles, and 501 related online comments, methods of applied thematic analysis revealed three main themes which captured the beliefs that (a) victims of bullying are weak, (b) perpetrators of bullying are evil, and (c) bullying is a normal and, in some ways, acceptable behavior. Such findings illustrate the role that societal beliefs play in shaping the environment in which bullying occurs, and have important implications for future bullying research and interventions.